Public perception of media social responsibility in developing countries: a case study of Albania - Skana, Pranvera; Gjerazi, Blerina (Frontiers in Communication, 2024)
This study delves into public perceptions of media social responsibility within the contemporary Albanian media landscape. Through a comprehensive analysis of various factors, the study identifies the prevailing principles that the public deems crucial for the media's social responsibility and how these principles can enhance the media's contribution to society. A structured questionnaire was used to capture a wide range of public perceptions, with 1,321 questionnaires filled out. These questionnaires were distributed using a face-to-face method across five major urban centers in Albania, ensuring a comprehensive and representative sample of public viewpoints. The distribution method employed a stratified sampling approach to ensure diverse representation across different demographic groups. Additionally, employing a mixed-methods approach, the research includes qualitative interviews with 20 influential stakeholders, including media directors, professors, analysts, and media researchers. Purposive sampling was utilized to select stakeholders representing various sectors of the media landscape. Rigorous measures were taken to mitigate data pollution, including thorough interviewer training and constant monitoring of data quality. An overarching thematic analysis was conducted to identify common themes and patterns across the qualitative interviews, complementing the quantitative findings. To gain further insights, we purposefully selected and conducted a focus group with 28 journalists from various media platforms. The sampling method for the focus group involved purposive sampling to ensure representation from diverse media backgrounds and experiences. Data collected from the focus group underwent thematic analysis to identify common themes and patterns, contributing to an overarching qualitative analysis. The empirical findings reveal that the media's social responsibility in Albania does not fully adhere to the expected standards encompassing all relevant principles. Internal dynamics within media organizations and external forces from politics, economics, and society collectively influence this shortfall. The study highlights the importance of considering public perceptions and expectations in shaping media's social responsibility, emphasizing the need for substantial improvements. In conclusion, this research not only provides practical insights for media practitioners but also offers valuable perspectives for policymakers.